Aquaporins: New players in breast cancer progression and treatment response - Charlestin, Verodia; Fulkerson, Daniel; Arias Matus, Carlos E.; Walker, Zachary T.; Carthy, Kevin; Littlepage, Laurie E. (Frontiers in Oncology, 2022)
Aquaporins (AQPs) are a family of small transmembrane proteins that selectively transport water and other small molecules and ions following an osmotic gradient across cell plasma membranes. This enables them to regulate numerous functions including water homeostasis, fat metabolism, proliferation, migration, and adhesion. Previous structural and functional studies highlight a strong biological relationship between AQP protein expression, localization, and key biological functions in normal and cancer tissues, where aberrant AQP expression correlates with tumorigenesis and metastasis. In this review, we discuss the roles of AQP1, AQP3, AQP4, AQP5, and AQP7 in breast cancer progression and metastasis, including the role of AQPs in the tumor microenvironment, to highlight potential contributions of stromal-derived to epithelial-derived AQPs to breast cancer. Emerging evidence identifies AQPs as predictors of response to cancer therapy and as targets for increasing their sensitivity to treatment. However, these studies have not evaluated the requirements for protein structure on AQP function within the context of breast cancer. We also examine how AQPs contribute to a patient’s response to cancer treatment, existing AQP inhibitors and how AQPs could serve as novel predictive biomarkers of therapy response in breast cancer. Future studies also should evaluate AQP redundancy and compensation as mechanisms used to overcome aberrant AQP function. This review highlights the need for additional research into how AQPs contribute molecularly to therapeutic resistance and by altering the tumor microenvironment.